Digital Health Opportunities to Improve Primary Health Care in the Context of COVID-19 - Silva, Cícera Renata Diniz Vieira (2022)
©Cícera Renata Diniz Vieira Silva, Rayssa Horácio Lopes, Osvaldo de Goes Bay Jr, Claudia Santos Martiniano, Miguel Fuentealba-Torres, Ricardo Alexandre Arcêncio, Luís Velez Lapão, Sonia Dias, Severina Alice da Costa Uchoa. Originally published in JMIR Human Factors (https://humanfactors.jmir.org), 31.05.2022.